Transcriptionally distinct B cell profiles in systemic immune tissues and peritoneal cavity of Atlantic salmon (Salmo salar) infected with salmonid alphavirus subtype 3 - Jenberie, Shiferaw; Sandve, Simen Rød; To, Thu-Hien; Kent, Matthew Peter; Rimstad, Espen; Jørgensen, Jorunn B.; Jensen, Ingvill (Frontiers in Immunology, 2024)
Teleost B cells producing neutralizing antibodies contribute to protection against salmonid alphavirus (SAV) infection, the etiological agent of pancreas disease, thereby reducing mortality and disease severity. Our previous studies show differences in B cell responses between the systemic immune tissues (head kidney (HK) and spleen) and the peritoneal cavity (PerC) after intraperitoneal SAV3 infection in Atlantic salmon (Salmo salar) where the response in PerC dominates at the late time points. By employing the same infection model, we aimed to further characterize these B cells. Immunophenotyping of teleost B cells is challenging due to limited availability of markers; however, RNA-seq opens an opportunity to explore differences in transcriptomic responses of these cells. Our analysis identified 334, 259 and 613 differentially expressed genes (DEGs) in Atlantic salmon IgM+IgD+ B cells from HK, spleen, and PerC, respectively, at 6 weeks post SAV3 infection. Of these, only 34 were common to all the three immune sites. Additionally, out of the top 100 genes with the highest fold change in expression, only four genes were common across B cells from the three sites. Functional enrichment analyses of DEGs using KEGG and GO databases demonstrated differences in enriched innate immune signaling and the cytokine-cytokine interaction pathways in B cells across the sites, with varying numbers of genes involved. Overall, these findings show the presence of transcriptionally distinct B cell subsets with innate immune functions in HK, spleen and PerC of SAV3-infected Atlantic salmon. Further, our data provide new insights into the immunoregulatory role of fish B cells through the differential expression of various cytokine ligands and receptors and will be a useful resource for further studies into B cell immune compartments.